Pesticides exposure as etiological factors of Parkinson's disease and other neurodegenerative diseases—A mechanistic approach - Baltazar, Maria Teresa; Dinis-Oliveira, Ricardo Jorge; de Lourdes Bastos, Maria; Tsatsakis, Aristidis M.; Duarte, José Alberto; Carvalho, Félix (Toxicology letters, 2014)
•The review provides new information regarding the neurotoxicity mechanisms of herbicides and pesticides.•New perspectives concerning chronic pesticide exposure with amyotrophic lateral sclerosis.•Novel information regarding paraquat exposure and Parkinson's disease.•New insights regarding chronic pesticide exposure and Alzheimer's disease. The etiology of most neurodegenerative disorders is multifactorial and consists of an interaction between environmental factors and genetic predisposition. The role of pesticide exposure in neurodegenerative disease has long been suspected, but the specific causative agents and the mechanisms underlying are not fully understood. For the main neurodegenerative diseases such as Parkinson's disease, Alzheimer's disease and amyotrophic lateral sclerosis there are evidences linking their etiology with long-term/low-dose exposure to pesticides such as paraquat, maneb, dieldrin, pyrethroids and organophosphates. Most of these pesticides share common features, namely the ability to induce oxidative stress, mitochondrial dysfunction, α-synuclein fibrillization and neuronal cell loss. This review aims to clarify the role of pesticides as environmental risk factors in genesis of idiopathic PD and other neurological syndromes. For this purpose, the most relevant epidemiological and experimental data is highlighted in order to discuss the molecular mechanisms involved in neurodegeneration.